Perencanaan Ruang Kelas SDN 027 Cicadas Bandung - Sari, Sally Octaviana; Aisyah, Linda; Fadhila, Raisa (Jurnal Pengabdian Tri Bhakti, 2022)
Institution of education has important role to take part in solving problems in Bandung city community development. Population growth inBandung drives the impact of facility andinfrastructure addition, including in primaryschool facilities. The land area of school could not be expandable and so its insufficient and facility infrastructure because of its location among slums settlement and traditional market.The Departement of Eduaction and Cultural hassustainable programs for improving school facility and infrastructure. The facility and infrastructure of Sekolah Dasar Negeri 027 recently has not been longer proper for physical and capacity for teaching and learning activities. In this program, abdimas team helps to carry out the planning renovation and supervision assistance process of Sekolah Dasar Negeri 027. This program involves architect and civil engineer to plan, design, count the structure of new classrooms addition and also supervise the renovation for few room of Sekolah Dasar Negeri 027. The output of this activity is to fulfill the need of the SDN 027 community to carry out the teaching and learning process.